2015
DOI: 10.1177/0021998315597551
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of an organic–inorganic composite superabsorbent based on attapulgite

Abstract: A novel, low-cost, and eco-friendly organic-inorganic composite superabsorbent is successfully prepared in aqueous solution by graft copolymerization of partially neutralized acrylic acid (AA), polyvinyl alcohol (PVA), and attapulgite (APT) using ammonium persulfate (APS) as an initiator and N,N-methylenebisacrylamide (MBA) as a crosslinker. The structure and morphology of the composite superabsorbent are characterized by means of Fourier transform infrared, X-ray diffraction, field-emission scanning electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Alkali treatment improved WS surface roughness and specific surface area and reduced the encapsulation of WS by PVC matrix, so water molecules can be contact with WS more easily. The addition of ATP before and after alkali treatment reduced the composites' water absorption, because the ATP crystal bundle could serve as the additional cross‐linking point in the polymer network, and adding ATP enhanced the cross‐linking density, so that the spatial network through which water molecules penetrate became narrower and the water absorption decreased 59 . Also, ATP physically filled the pores between the interface of WS and PVC matrix, reduced composites' internal water storage space.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkali treatment improved WS surface roughness and specific surface area and reduced the encapsulation of WS by PVC matrix, so water molecules can be contact with WS more easily. The addition of ATP before and after alkali treatment reduced the composites' water absorption, because the ATP crystal bundle could serve as the additional cross‐linking point in the polymer network, and adding ATP enhanced the cross‐linking density, so that the spatial network through which water molecules penetrate became narrower and the water absorption decreased 59 . Also, ATP physically filled the pores between the interface of WS and PVC matrix, reduced composites' internal water storage space.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of ATP before and after alkali treatment reduced the composites' water absorption, because the ATP crystal bundle could serve as the additional cross-linking point in the polymer network, and adding ATP enhanced the cross-linking density, so that the spatial network through which water molecules penetrate became narrower and the water absorption decreased. 59 Also, ATP physically filled the pores between the interface of WS and PVC matrix, reduced composites' internal water storage space. The capillary transfer of water in the gap of the two-phase interface of the composites is one of the infiltration mechanisms, while ATP blocked the gap as a water transfer channel and inhibited the water penetration into composites deep layer, 60 conforming to the study by Vigneshwaran et al, 61 who added 20% red mud to the composites, and found that the water absorption decreased significantly, and adding red mud particles in the matrix hindered the diffusion of water molecules in the composites.…”
Section: Composites' Water Absorptionmentioning
confidence: 99%
“…Compared with bound water and half-bound water, free water has higher transferability and is easily lost under ultrasonic treatment. [27][28][29] Ultrasonic treatment can effectively improve the stability and water absorption of the composite materials. 30 Adding a certain amount of attapulgite to the composite material increases the number of hydrophilic functional groups, such as -COOH and -COOH, resulting in a higher percentage of bound and half-bound water in the composite superabsorbent than free water, which signicantly enhances the water retention ability of the formed polymer.…”
Section: Effect Of Solution Ph On Water Absorbencymentioning
confidence: 99%
“…The shell of the slow-release materials used in this study was manufactured using attapulgite, diatomite, and Portland cement. Attapulgite is a type of hydrated octahedral layered magnesium aluminum silicate absorbent mineral with exchangeable cations and reactive −OH groups on its surface [66]. Diatomite (SiO2•nH2O) is a fine granulated siliceous sedimentary rock, mainly composed of diatom shells with smaller proportions of other sediments like clay and quartz [67].…”
Section: Analysis Of the Longevity Of The Slow-release Materialsmentioning
confidence: 99%